2019
DOI: 10.3389/fphys.2019.00231
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of the Interaction Gut Microbiota – Sympathetic Nervous System in the Regulation of Blood Pressure

Abstract: Association between gut dysbiosis and neurogenic diseases, such as hypertension, has been described. The aim of this study was to investigate whether changes in the gut microbiota alter gut-brain interactions inducing changes in blood pressure (BP). Recipient normotensive Wistar-Kyoto (WKY) and spontaneously hypertensive rats (SHR) were orally gavaged with donor fecal contents from SHR and WKY. We divided the animals into four groups: WKY transplanted with WKY microbiota (W-W), SHR with SHR (S-S), WKY with SHR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
165
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 176 publications
(175 citation statements)
references
References 48 publications
6
165
3
1
Order By: Relevance
“…The FMT to recipient rats was performed as previously reported (Toral et al, , ). Faecal contents were diluted 1:20 in sterile PBS and centrifuged at 60 g for 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The FMT to recipient rats was performed as previously reported (Toral et al, , ). Faecal contents were diluted 1:20 in sterile PBS and centrifuged at 60 g for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been demonstrated that the normal gut microbiota may influence BP. A direct association between gut microbiota and hypertension in both animal models and humans has been described (Yang et al, ; Kim et al, , Toral et al, , , Sun et al, ). In contrast, Karbach et al () showed that BP was not different between germ‐free and conventionally raised mice, which is consistent with previous observations describing no effect on BP after dramatic reduction in faecal microbial biomass induced by antibiotic treatment (Pluznick et al, ).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations